2014
DOI: 10.1620/tjem.234.41
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Caloric Restriction prior to Pregnancy Increases the Body Weight of the Second-Generation Male Offspring and Shortens Their Longevity in Rats

Abstract: Maternal undernutrition can affect offspring's physical status and various health parameters that might be transmittable across several generations. Many studies have focused on undernutrition throughout pregnancy, whereas maternal undernutrition prior to pregnancy is not sufficiently studied. The objective of our study was to explore the effects of food restriction prior to and during pregnancy on body weight and longevity of the second generation offspring. Adult female Wistar rats ("F0" generation) were 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Global nutrient restriction in one generation also resulted in transgenerational effect with BP increased in male offspring of the F2 and F3 generations despite the absence of additional insult during their gestational period [88]. The effect of exposure to maternal undernutrition in the F1 also impaired vascular function in the F1 offspring and subsequent generations [88] Nutrient restriction initiated prior to pregnancy also reduced life expectancy in the second-generation male offspring [89]. Thus, these studies suggested that fetal exposure to nutrient restriction in one generation not only increased CV risk in the F1 generation, but also transmitted that risk to the next generations of male offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Global nutrient restriction in one generation also resulted in transgenerational effect with BP increased in male offspring of the F2 and F3 generations despite the absence of additional insult during their gestational period [88]. The effect of exposure to maternal undernutrition in the F1 also impaired vascular function in the F1 offspring and subsequent generations [88] Nutrient restriction initiated prior to pregnancy also reduced life expectancy in the second-generation male offspring [89]. Thus, these studies suggested that fetal exposure to nutrient restriction in one generation not only increased CV risk in the F1 generation, but also transmitted that risk to the next generations of male offspring.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, only one study provides direct evidence that rodent longevity can be transmitted across generations. In this study, dietary restriction during preconceptional or both preconceptional and gestational periods resulted in increased body weight and life shortening in the second-generation male, but not the female offspring [ 69 ].…”
Section: Findings From Animal Studiesmentioning
confidence: 99%
“…In fact, several studies in rats show that offspring born to mothers fed on a low-protein diet during pregnancy have shorter lifespans [ 47 49 ] and become less fertile at a younger age [ 49 51 ] than those fed on a normal diet. Moreover, recent studies suggest that maternal nutrient restriction may also result in reduced F2 offspring lifespan [ 52 ] and accelerated reproductive ageing [ 53 ]. This accelerated ageing and loss of fertility may be linked to increased oxidative stress [ 51 , 54 ], which is known to contribute to ageing.…”
Section: Inter- and Trans-generational Inheritance Of Lifespan And Prmentioning
confidence: 99%